2019
DOI: 10.1007/s13197-018-3540-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of microwave-assisted extraction of bioactive compounds from New Zealand and Chinese Asparagus officinalis L. roots

Abstract: The extraction of total phenolics (TPC), total flavonoids content (TFC), total saponins content (TSC), and caffeic acid (AC) contents of asparagus roots extract (ARE) from New Zealand and Chinese AR cultivars was optimized following a microwave-assisted extraction combined with central composite design. The determination of AC was conducted by HPLC in samples extracted under the optimum extraction conditions. The optimal variables for ethanol extraction generated a maximum TPC, TFC and TSC of optimal results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The optimal conditions for the MAE of TPCs from S. chamaecyparissus were as fo lows: 65% methanol in the water at pH 2, 100 °C temperature, and 15/0.2 mL/g as th optimum solvent-sample ratio. The percentage of solvent is at a rather mild level, whic is in accordance with many recent publications [23,30,31,43]. pH levels lower than 2 we The optimal conditions for the MAE of TPCs from S. chamaecyparissus were as follows: 65% methanol in the water at pH 2, 100 • C temperature, and 15/0.2 mL/g as the optimum solvent-sample ratio.…”
Section: Optimization Of the Microwave-assisted Extraction (Mae) Conditionssupporting
confidence: 87%
See 1 more Smart Citation
“…The optimal conditions for the MAE of TPCs from S. chamaecyparissus were as fo lows: 65% methanol in the water at pH 2, 100 °C temperature, and 15/0.2 mL/g as th optimum solvent-sample ratio. The percentage of solvent is at a rather mild level, whic is in accordance with many recent publications [23,30,31,43]. pH levels lower than 2 we The optimal conditions for the MAE of TPCs from S. chamaecyparissus were as follows: 65% methanol in the water at pH 2, 100 • C temperature, and 15/0.2 mL/g as the optimum solvent-sample ratio.…”
Section: Optimization Of the Microwave-assisted Extraction (Mae) Conditionssupporting
confidence: 87%
“…These results are in agreement with those obtained by V. González de Peredo et al, (2018) [31], who reported that solvent composition is one of the most influential factors on the extraction of TPC from myrtle (Myrtus communis L.), and Vázquez-Espinosa et al, (2018) [30] who reported that the extraction temperature and the solvent percentage were the most influential parameters on the extraction of TPC from maqui berry (Aristotelia chilensis). In the same way, Zhang et al, (2019) [43] proved that the concentration of the solvent and the solvent-sample ratio are the most influential factors on the extraction of TPC from Asparagus officinalis L. roots.…”
Section: Optimization Of the Microwave-assisted Extraction (Mae) Conditionsmentioning
confidence: 89%
“…The changing trends of three parameters of Akebia trifoliate peel extract were also similar to those reported in the literature [ 10 ]. The solvent-to-material ratio was considered to be one of the most important factors affecting the extraction yields of phenolic compounds [ 20 , 21 ]. A larger ratio of solvent-to-material was conducive to the rapid release of the intracellular substances and enhanced extraction yield [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The roots also contain small amounts of resins and essential oils, which can be easily removed with petroleum ether and an aqueous solution of potassium, respectively [ 7 ]. Withania somnifera [ 29 ], Scutellaria baicalensis Georgi [ 30 ], Pueraria lobatae [ 31 ], and Asparagus officinalis [ 32 ] are some examples of roots that have been used as natural sources for the obtention of flavonoids.…”
Section: Natural Sources Of Flavonoidsmentioning
confidence: 99%